AN ANALYSIS OF READING SPEED OF STUDENT IN BIMBEL ADZKIA PADANG - Astari Ningsih; Melvina; Sesmiyanti (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The aim of this research is to determine reading speed and reading comprehension at Tutoring Adzkia Padang. This research method is a descriptive method. The population in this study were 101 Adzkia official tutoring students with a sample of 20 students. This research instrument is a text containing 20 questions. The results of this research were that 50% of students had a basic level of reading speed, 40% of students had an average level of adult reading speed and 10% of students had a level slightly above average reading speed with the majority of students at Bimbel Adzkia Padang having adult reading speed. Then, their reading comprehension level is that the average student is categorized as good in detail where 30% of students are categorized as having a very good level of reading comprehension, 30% of students have good reading comprehension, 10% of students are categorized as having average reading comprehension and 30% of students have a poor reading comprehension level and 0% of students have a very poor reading comprehension level. The conclusion of this research is that the average student has a reading speed in the adult reading speed category and reading comprehension in the good category.